CANDIDATE MEDICINAL PLANT SPECIES OF DJIBOUTIAN PHARMACOPEIA FOR TESTING PHARMACOLOGICAL ACTIVITIES ON COMMON MICROBIAL DISEASES - Abdoul-latif, Fatouma Mohamed; Osman, Djaltou Aboubaker; Fourreh, Abdirahman Elmi; Hassan-Abdallah, Alshaimaa; Merito, Ali; Hassan, Souad; Asfaw, Zemede; Kelbessa, Ensermu (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The aim of the study was to conduct an ethnobotanical study focused on the medicinal plants used in Randa (Djibouti) for testing pharmacological activities on common microbial diseases. Methods: Plant Ratio (PR), Index of Performance (IP) and the high Informant Consensus Factors (ICF) were calculated to select candidate medicinal species with a pharmacological potential. Results: From this previous work, it was found that the high Informant Consensus Factors, ICF (0.82) for the category of microbial diseases turned out to merit further perusal. The findings particularly gave an imminent insight that stimulated additional investigations and analyses. Different factors, including Plant Ratio (PR) and Index of Performance (IP) were employed for comparison leading to the selection of 18 candidates species, for subsequent pharmacological screening, and testing for antimicrobial activities. Comparison of the information with that accessed from the literature implicitly hinted that the Djiboutian traditional medical system shares much in common with other traditional medical systems. At least six out of the 18 species have not been pharmacologically tested before. Conclusion: The comparison of differents factors (IP2, PR and FL') of plants screening have showed that 18 plants species of Randa region, have good healing potential for infectious diseases. This may inspire continued research to build a comprehensive ethnobotanical and ethnopharmacological profiles of the species anticipated to be of the most promising potential for Djibouti and beyond.